Utility of urinary gram stain as a diagnostic method for urinary tract infection - Anchinmane, Vyankatesh T.; Preet, Kamal; Sankhe, Shilpa (International Journal of Research in Medical Sciences, 2018)
Background: Urinary tract infection (UTI) is one of the most common infections in humans. Timely diagnosis and treatment are necessary to reduce the complications from UTI. Urine culture is still the gold standard diagnostic test for UTI, however it is costly and time consuming. The present study was conducted to compare the utility of urinary gram stain, microscopy of centrifuged urine sample and urine culture for the diagnosis of UTI. Methods: 100 urine samples were processed for gram stain, culture and microscopy. Urinary gram stain findings were correlated with microscopy and culture results. Using urine culture as gold standard, the sensitivity, specificity, accuracy, positive predictive value (PPV) and negative predictive value (NPV) of urinary gram stain were assessed for the diagnosis of UTI. Results: The accuracy of urinary gram stain for detection of UTI was 97%. Conclusions: Urinary gram stain is a reliable diagnostic test for early detection of UTI.